1990
DOI: 10.1111/j.1365-2044.1990.tb14564.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood contamination of anaesthetic and related staff

Abstract: Summary Key wordsInfection; Hepatitis B, acquired immune deficiency syndrome. Anaesthetists; complications.The Association of Anaesthetists advises all anaesthetists to wear gloves in the operating theatre for vessel cannulation and insertion or removal of airways and tracheal tubes.' The Expert Advisory Group on the acquired immune deficiency syndrome (AIDS) also recommends gloves to be worn, as a minimum protective measure, for any procedures where there is likely to be contact with blood.2 This advice was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
19
0
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 6 publications
2
19
0
1
Order By: Relevance
“…Harrison et al reported that anaesthetists prefer sterile surgical gloves to protective gloves even for simple invasive procedures such as puncturing a peripheral vein because they feel surgical gloves are of better quality [4]. Various authors and national societies have declared the use of sterile gloves to be standard procedure, although it is not always clear at what degree of invasiveness sterile gloves become a necessity [1,2,7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Harrison et al reported that anaesthetists prefer sterile surgical gloves to protective gloves even for simple invasive procedures such as puncturing a peripheral vein because they feel surgical gloves are of better quality [4]. Various authors and national societies have declared the use of sterile gloves to be standard procedure, although it is not always clear at what degree of invasiveness sterile gloves become a necessity [1,2,7].…”
Section: Discussionmentioning
confidence: 99%
“…Noticeable impairment of touch sensitivity caused by wearing gloves increases the number of unsuccessful punctures, reduces patient comfort and also reduces the physician's willingness to wear gloves [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall incidence of glove wearing at the Bristol Royal Infirmary is probably much higher than in previous studies in 1989 [9] and 1992 [6, 121. However, despite repeated recommendations that gloves should be worn routinely and education of the risks of hepatitis and HIV, the incidence of glove wearing does not approach 100%.…”
Section: Discussionmentioning
confidence: 67%
“…The risk of needle stick injury has been well defined [5,6] and measures have been recommended to reduce the incidence [7]. It is recommended that protective gloves should be worn during the administration of anaesthesia [8], although it is well known that many anaesthetists choose to ignore this recommendation and have a high risk of direct contact with patients' blood [9]. It has been suggested that the prevalence of hepatitis B seroconversion is higher in anaesthetists who wear gloves only when performing sterile procedures [ 101.…”
mentioning
confidence: 99%